Fundamentals of futures and options markets - Hull, John C. (Pearson, 2017)
This book does a great job at clearly teaching the basics of forwards/futures and options markets. While there are a handful of summary questions at the end of each chapter that have answers in the back of the book, the overwhelming majority of answers to the end of chapter practice problems are not. In order to use this book properly and get the most out of it, the study guide is a necessity. Other than that, it's a great textbook.